Q:

Part 1 (Unit 2): Subtract Polynomials:(3−6n5−8n4)−(−6n4−3n−8n5)Part 2 (Unit 3): Solve this quadratic equation. Show all your work (steps) for full credit:4x2−2x−5=0

Accepted Solution

A:
Part 1
 We have the following polynomials:
 (3-6n5-8n4)
 (-6n4-3n-8n5)
 Subtracting the polynomials we have:
 (3-6n5-8n4) - (- 6n4-3n-8n5)
 n5 (-6 + 8) + n4 (-8 + 6) + 3n + 3
 Rewriting:
 2n5 - 2n4 + 3n + 3

 Part 2
 For this case we have the following polynomial:
 4x2-2x-5 = 0
 Using resolver we have:
 x = (- b +/- root (b ^ 2 - 4 * a * c)) / (2 * a)
 x = (- (- 2) +/- root ((- 2) ^ 2 - 4 * 4 * (- 5))) / (2 * 4)
 x = (2 +/- root (4 + 80)) / (8)
 x = (2 +/- root (84)) / (8)
 x = (2 +/- root (4 * 21)) / (8)
 x = (2 +/- 2raiz (21)) / (8)
 x = (1 +/- root (21)) / (4)
 The roots are:
 x1 = (1 + root (21)) / (4)
 x2 = (1 - root (21)) / (4)